Short- and long-term outcomes of self-expanding metallic stent placement vs. emergency surgery for malignant colorectal obstruction - Yagawa, Yusuke (Mol Clin Oncol, 2021)
The European Society of Gastrointestinal Endoscopy does not recommend self-expanding metal stent (SEMS) placement as a bridge to surgery (BTS) for malignant colorectal obstruction (MCRO). However, no universally accepted consensus has been determined. The present study aimed to evaluate the short- and long-term outcomes of SEMS placement vs. emergency surgery (ES) for MCRO. Surgical resection of colorectal cancer was performed in 3,840 patients between April 2001 and June 2016. Of these, 93 patients had MCRO requiring emergency decompression. Only patients in whom the colorectal lesion was ultimately resected were included; thus, the present study included 62 patients treated with MCRO via SEMS placement as a BTS (n=25) or via ES (n=37). The rates of laparoscopic surgery, primary anastomosis, stoma formation, lymph node dissection, adverse events, 30-day mortality and disease-free survival were evaluated. The clinical success rate of SEMS placement was 92.0% (23/25). Compared with the ES group, the SEMS group had higher rates of laparoscopic surgery (68.0 vs. 2.7%; P<0.001) and primary anastomosis (88.0 vs. 51.4%; P=0.003), a greater number of dissected lymph nodes (30 vs. 18; P=0.001), and lower incidences of stoma formation (24.0 vs. 67.6%; P=0.002) and overall adverse events (24.0 vs. 62.2%; P=0.004). The 30-day mortality and disease-free survival of the SEMS group were not significantly different to that of the ES group (0 vs. 2.7%; P=1.000; log-rank test; P=0.10). In conclusion, as long as adverse events such as perforation are minimized, SEMS placement as a BTS could be a first treatment option for MCRO. The present study is registered in the University Hospital Medical Network Clinical Trials Registry (UMIN R000034868).